Corporate Social Responsibility in Cultivating Customer Loyalty: Intuitions from the Banking Industry - Shrestha, Sajeeb Kumar; Paudel, Amrit Kumar; Mahat, Dipak; Karki, Tej Bahadur; Neupane, Dasarath (NPRC Journal of Multidisciplinary Research, 2025)
The purpose of the study is to analyze the impact of CSR on enhancing customer loyalty for banking institutions. The design of the research adopted for the study was descriptive and causal. For data collection, structured questionnaires were designed and administered via survey. The respondents targeted for the study were social media users, from which a sample size of 103 was collected through convenience sampling. The data were then analyzed in detail by means of reliability analysis, descriptive statistics, correlation analysis, and regression analysis. Results showed that CSR initiatives, customer-centric approach, and economic benefits significantly influence customer loyalty.